Cranch family papers
Correspondence, poetry, and other items. Correspondents include John Adams, John Quincy Adams, Abigail Adams, Noah Webster, William Cranch, Eunice Paine, and Josiah Quincy.
Collection material in English.
Keywords: Adams, Abigail, -- 1744-1818 -- Correspondence; Adams, John, -- 1735-1826 -- Correspondence; Adams, John Quincy, -- 1767-1848 -- Correspondence; Cranch, William, -- 1769-1855 -- Correspondence; Paine, Eunice -- Correspondence; Quincy, Josiah, -- 1772-1864 -- Correspondence; Webster, Noah, -- 1758-1843 -- Correspondence; Cranch family